GEO-IT Marketing – The new way to do marketing - Macedo Obiol, Alejandro (2017)
This company’s aim is to provide a new way of doing marketing by using specific hardware to analyse the behaviours of people inside indoor spaces where GPS and Phone triangulations do not work. The in-house software uses a special hardware to triangulate mobile phones when the Wi-Fi or Bluetooth are enabled. This information is legal as the devices are never identified and the information is stored with a unique encrypted pattern that assures that any identifications cannot be linked to the phone itself. This information can be used then for data analysis activities. The company will explore 3 main business activities: In the first stage, we will deploy a specific hardware within the shopping industry to allow our software to follow the patterns of people moves. With this information, we will provide marketing services and data mining services to shoppers and shops. After this, the company will increase business activities to security and event management, in this area we will provide services using our hardware and software to recognise people and organise flows of people. The last activity will be using all our learned knowledge from the previous activities to be able to generate simulations of behaviours and help architects and governments to analyse how crowds will behave.